Preparation of a stoichiometric molecularly imprinted polymer for auramine O and application in solid‐phase extraction. Issue 8 (6th March 2019) - Pataer, Parezhati; Muhammad, Turghun; Turahun, Yunusjan; Yang, Wenwu; Aihebaier, Sailemayi; Wubulikasimu, Muyasier; Chen, Lingxin
Abstract: We describe a stoichiometric approach to the synthesis of molecularly imprinted polymers specific for auramine O. Using the stoichiometric interaction in molecular imprinting, no excess of binding sites is necessary and binding sites are only located inside the imprinted cavities. The free base of the template was obtained to facilitate the interaction with the monomers. Itaconic acid was selected as the functional monomer, and stoichiometric ratio of the interaction with the free base was investigated. The molecularly imprinted polymer preparation conditions such as cross‐linker, molar ratio, porogen were optimized as divinylbenzene, 1:2:20 and chloroform/N, N‐dimethylformamide, respectively. Under the optimum conditions, a good imprinting effect and very high selectivity were achieved. A solid‐phase extraction method was developed using the molecularly imprinted polymers as a sorbent and extraction procedure was optimized. The solid‐phase extraction method showed a high extraction recovery for auramine O in its hydrochloride form and free form compared to its analogues. The results strongly indicated that stoichiometric imprinting is an efficient method for development of high selectivity molecularly imprinted polymers for auramine O.